Genome-Wide Analysis of the YABBY Gene Family in Grapevine and Functional Characterization of VvYABBY4 - Zhang, Songlin; Wang, Li; Sun, Xiaomeng; Li, Yunduan; Yao, Jin; Nocker, Steve van; Wang, Xiping (Frontiers in Plant Science, 2019)
Genes of the plant-specific YABBY transcription factor family have various roles including lateral organ development, establishment of dorsoventral polarity and response to abiotic stress. In this study, we carried out a genomic census of YABBY genes in grapevine (Vitis vinifera) and characterized their expression pattern during ovule development. We identified seven YABBY genes and classified them into five subfamilies, based on peptide sequence, similarity of exon-intron structure and composition of peptide sequence motifs. Analysis of YABBY gene expression in various grapevine structures and organs suggested that these genes function in diverse aspects of development and physiology. Analysis of expression during ovule development in four cultivars showed that one gene, VvYABBY4, was preferentially expressed during the period of ovule abortion in seedless cultivars. Transgenic expression of VvYABBY4 in tomato conferred reduced plant stature, dark green leaves, elongated pistil, and reduced size of fruit and seeds. Reduced seed size was associated with smaller endosperm cells. Expression of VvYABBY4 also affected expression of numerous tomato genes with presumed roles in seed development. This data suggest the potential for VvYABBY4 to influence seed development in grapevine, which may impact seedless grape breeding.